Faktor penyebab rendahnya pemanfaatan jurnal elektronik di Perpustakaan Universitas Gadjah Mada oleh mahasiswa Sekolah Pascasarjana - Fitri Handayani (Berkala Ilmu Perpustakaan dan Informasi, 2021)
Introduction. This study aims to examine the inhibiting factors of the use of electronic journals atthe Universitas Gadjah Mada (UGM) Library by UGM graduate school students. The study used Weber's information system model theory with the following variables: system quality, information quality, user training, perceived usefulness, perceived ease of use, computer self-efficacy, information system use, individual impact and information system satisfaction. Data Collection Methods. This study used surveys with a quantitative approach. and observations. Results and Discussion. The results of this study showed that the inhibiting factors of electronic journals at the UGM Library was the difficulties in using information systems electronic journals. This resulted that the students were less confident and rarely to access and utilize electronic journals due to their lack of understanding and skilss in using computers or e-Journal information system. Conclusion. The low utilization of the electronic journal is related to the quality of information system (system quality), user perceived difficulties when accessing the electronic journal Information system (perceived easy of use) and the user's ability to use the computer (computer self-efficacy).